Identification of peptides sequence and conformation contributed to potential allergenicity of main allergens in yogurts - Huang, Meijia; Yang, Fan; Wu, Yong; Meng, Xuanyi; Shi, Linbo; Chen, Hongbing; Li, Xin (Frontiers in Nutrition, 2023)
Yogurts provide a good source of nutrition and may induce tolerance in people with cow’s milk allergy (CMA). This study aimed to investigate the changes in the allergenicity of main allergens in the different yogurts which provide a reference for people with a high risk of CMA, and analyze the epitopes of major allergen peptides in yogurt. We assessed the degradation and the allergenic properties of major allergens in six commercial yogurts and fresh milk. The degradation of major allergens was analyzed by SDS-PAGE and RP-HPLC. Western blot and ELISA experiments detected allergenic characteristics by using specific sera. The results showed that β-lactoglobulin (β-LG) and α-lactalbumin (α-LA) were obviously degraded in yogurts but casein was still present in abundance, which indicated that the proteases in yogurts were specific to whey proteins. IgE and IgG binding ability of major allergens were obviously reduced in yogurts, especially GM yogurt. In addition, 17 peptides of major allergens in GM yogurt were identified by LC-MS/MS and most of them were located in the interior of the spatial structure of proteins. Among them, 8 peptides had specific biological functions for health benefits, such as antibacterial, antioxidant, and ACE-inhibitory. We also found that 6 and 14 IgE epitopes of β-LG and casein were destroyed in GM yogurt, which could lead to the reduction of allergenicity. Meanwhile, peptides (β-LG (AA15-40), αS1-casein (AA120-151, AA125-151)) also preserved T cell epitopes, which might also induce the development of oral tolerance. Therefore, this study suggested that the sequence and conformation of peptides in yogurts contributed to hypoallergenicity.